2016
DOI: 10.1039/c6cp01437b
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection and triplet energy transfer in higher plants: the role of electronic and nuclear fluctuations

Abstract: Abstract-The quenching of Chlorophyll triplets by triplet energy transfer (TET) to carotenoids is one of the photoprotection strategies in photosynthetic organisms, and prevents singlet oxygen formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…Triplet-triplet energy transfer from chlorophylls to carotenoids is mediated by Dexter mechanism (Dexter, 1953), which needs overlap between the electron clouds of the donor and acceptor. When distance or orientation of carotenoid and chlorophyll is changed, the capability of carotenoids to quench excitation energy of triplet chlorophylls is diminished (Cupellini et al, 2016). Under such conditions, when O 2 is in the proximity of triplet chlorophyll, the transfer of excitation energy from triplet chlorophyll to O 2 forms 1 O 2 .…”
Section: High Lightmentioning
confidence: 99%
“…Triplet-triplet energy transfer from chlorophylls to carotenoids is mediated by Dexter mechanism (Dexter, 1953), which needs overlap between the electron clouds of the donor and acceptor. When distance or orientation of carotenoid and chlorophyll is changed, the capability of carotenoids to quench excitation energy of triplet chlorophylls is diminished (Cupellini et al, 2016). Under such conditions, when O 2 is in the proximity of triplet chlorophyll, the transfer of excitation energy from triplet chlorophyll to O 2 forms 1 O 2 .…”
Section: High Lightmentioning
confidence: 99%
“…Investigating the role of TET in photoprotection is thus more complicated, as the relevant coupling term cannot be expressed with the approximation presented in the previous section. Atomistic investigations of TET in photoprotection [120,121] have thus employed quantum chemical methods, in conjunction to a diabatization scheme called Fragment Spin Difference [122] to compute the TET coupling. One of the main findings of these atomistic simulations is that TET rates can be strongly enhanced by geometrical fluctuations [121], due to the steep distance dependence of Dexter's mechanism.…”
Section: From the Lh Function To Its Photoregulationmentioning
confidence: 99%
“…Indeed, different MD-based studies have shown that structural fluctuations significantly enhance TEET dynamics, which can be explained on the basis of the tails observed in the coupling distributions. 98,100,101 Regarding SEET couplings, in systems where the D/A molecules are held in a relatively rigid conformation, for example, the chlorophylls in the CP29 complex, the fluctuations display a more Gaussian distribution, as shown in Figure 4c, and a reasonable estimate of the rate can often be achieved by computing the coupling from a static structure. For example, a number of studies have been able to describe the light-harvesting properties of photosynthetic complexes based on static structures, although others adopt MD-averaged values.…”
Section: The Role Of Fluctuationsmentioning
confidence: 99%
“…83 (b) triplet-triplet energy transfer (TEET) coupling between two adenines in a polyA-polyT DNA sequence, 98 (c) SEET coupling between chlorophylls a603 and a609 in the CP29 photosynthetic complex, 79 (d) TEET coupling between chlorophyll a603 and violaxanthin in the CP29 photosynthetic complex. 101 In FRET systems where conformational transitions and fluorophore orientational dynamics can drastically change the mutual distance and orientation between the D/A chromophores, MD simulations are particularly useful in disentangling dynamic and static coupling fluctuations in the prediction of EET efficiencies. 17,19,38 If the coupling fluctuations along the trajectory are fast compared with the donor excited-state decay (dynamic averaging regime), the efficiency can be calculated using the averaged rate constant:…”
Section: The Role Of Fluctuationsmentioning
confidence: 99%
See 1 more Smart Citation